Towards Inclusive Education in Vocational Education: - Development Project as a Change Agent - Mäkinen, Maija; Alemu, Yekunoamlak; Abebe, Azmera Kebede (Ammattikasvatuksen aikakauskirja, 2019)
This article examines how an international project can have an impact on the educational development of the partner country, with the TECIP project (Teacher Educators in Higher Education as Catalysts for Inclusive Practices) being an example. It is a collaborative project aiming at promoting inclusive education in Technical and Vocational Education and Training (TVET) teacher education in Ethiopia. The project is considered a developmental agent that can have an impact on the attitudes, skills and knowledge of actors, which in turn can lead to sustainable changes in inclusive practices in TVET. The project’s target groups were TVET teacher trainers, TVET administration and TVET teachers at the grassroots level at vocational colleges. The data was gathered from three baseline studies: from feedback of three trainings in 2017–2018 as well as from two monitoring visit rounds to ten TVET Colleges. After analysis, studies showed that project activities had started a development process that the actors will continue in their respective organisations. Some improvement was observed in TVET Colleges after the trainings, e.g. awareness raising trainings were organised and construction of ramps was undertaken in some colleges. Nevertheless, the attitude change towards students with disabilities and the physical accessibility did not reach the desired level. Thus, there is a need to continue and strengthen partnership in order to promote sustainable inclusive practices in Technical and Vocational Education and Training in Ethiopia.